Scientific examination of documents : methods and techniques - Ellen, David; Davies, Christopher; Day, Stephen; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
Revised and expanded to reflect the most recent innovations in the field, The Scientific Examination of Documents, Fourth Edition is a handy, accessible volume detailing current best-practices for forensic document examination. Since the first edition published in 1989, there have been drastic changes in the field of forensic document examination both from the use of the analytic techniques available to the professional examiner and the changes to technology in office and printing equipment and inks. The purpose of analyzing any material used in the production of a questioned document, such as an ink or a piece of paper, is to compare it with another material elsewhere in the questioned document itself or on another document to determine whether or not they share a common origin. There may also be a need to provide information for the investigator about the possible origins of the document.
chapter 1 Introduction -- chapter 2 Handwriting: The Variations between Normal Writings -- chapter 3 Handwriting: Accidental and Deliberate Modification -- chapter 4 Handwriting: The Purposes and Principles of Scientific Examination -- chapter 5 Handwriting: The Collection of Samples -- chapter 6 Typewriting and Typescripts -- chapter 7 The Materials of Handwritten Documents: Substances and Techniques -- chapter 8 The Examination of Printed and Photocopied Documents -- chapter 9 Incidental Marks and Other Scientific Examinations -- chapter 10 The Functions of Imaging in Document Examination and Other Special Techniques -- chapter 11 Document Examination in Court.
Keywords: LAW / Forensic Science; Writing -- Identification